Causation of permanent brachial plexus injuries to the anterior arm after shoulder dystocia – Literature review. Issue 2 (April 2019) - Draycott, Tim; Kubiak, Kerstin; Arthur, Endurance; Crofts, Joanna
Not all neonatal brachial plexus injuries should be deemed the fault of the accoucheur. However, there is a small (<10%) subset of neonatal brachial plexus injuries that are related to excessive traction by the accoucheur: permanent injuries to the anterior arm after SD. The position regarding posterior injuries remains predominantly the same; if the injury is to the posterior shoulder, the injury is likely to have been caused by maternal propulsion against the sacral promontory before the foetal head is delivered, rather than excessive and inappropriate traction. However, there is no reliable evidence that a combination of maternal propulsion and diagnostic traction alone causes significant and permanent injury to the anterior shoulder after shoulder dystocia. This was recognised in Deith vs. Lanarkshire where the judge found: that where there is a severe injury to an anterior arm after SD, excessive traction is overwhelmingly likely to be the cause.